Analysis of The Efficiency Allocative of The Tabela Rice Farming System in Tondowolio Village, Tanggetada Sub-District, Kolaka - Syahrir Syahrir; Muhtar Amin; Eka Safitri (Agribusiness Journal, 2020)
This research aims to determine the efficiency of the use of factors (seeds, fertilizers, pesticides, the number of workers) allocatively in the wetland rice farming system in the Tondowolio Village, Tanggetada District, Kolaka Regency; This is to determine the risk of lowland rice farming with a table system in Tondowolio Village, Tanggetada District, Kolaka Regency. This research was conducted in Tondowolio Village, Tanggetada Subdistrict, Kolaka Regency, using an analysis of allocative efficiency and farm risk. Results: The seeds with an NPMx / Px value of 499.9 1 so that the use of seeds in the research area was not efficient, the allocative efficiency of fertilizers with an NPMx / Px value was 6.18 1 so that the use of fertilizers in the research area was not efficient, the allocative efficiency of pesticides with a value NPMx / Px of 1357.56 1 so that the use of seeds in the research area is not efficient, the allocative efficiency of HOK (labor) with an NPMx / Px value of -237.75 1 so that the use of seeds in the research area is inefficient. Farm risk analysis obtained a production risk value of 0.41, a price risk of 0.008 and a risk of profit of 0.41. The value of production risk, price risk, and profit risk is directly proportional to the risk faced by farmers, the greater the coefficient of variation obtained, the greater the risk that must be borne by farmers, and vice versa.